Assessment of Physical Suitability of Soils for Vegetable Production in the Libga Irrigation Scheme, Northern Region, Ghana Using the Analytic Hierarchy Process and Weighted Overlay Analysis - Yakubu Saaka Zakaria; Abdul-Ganiyu Shaibu; Bernard N Baatuuwie (Turkish Journal of Agriculture: Food Science and Technology)
Assessing the suitability of soils for agricultural production is critical in promoting sustainable agriculture. Knowledge gained from soil suitability analysis provides the sound basis for making informed decisions about soil management and crop selection in a given area. In view of this, this study was carried out to assess the physical suitability of soils in the Libga Irrigation Scheme for the sustainable cultivation of jute mallow (Corchorus olitorius), tomato (Solanum lycoperscum L.) and cabbage (Brassica oleracea var capitata). Soil samples were collected at 0–30 cm and 30–60 cm depths from 50 geo-referenced points located at the nodes of a 100 m × 100 m regular grid. Particle size distribution, bulk density, total porosity, field capacity, permanent wilting point, available water capacity, saturated hydraulic conductivity, electrical conductivity and pH were determined following standard laboratory protocols at the AGSSIP Laboratory of the University for Development Studies, Nyankpala campus, Ghana. Weighting of soil properties was achieved through the analytic hierarchy process (AHP). Soil suitability maps for the selected crops were produced using weighted overlay analysis in ArcGIS (10.5). The results showed that generally about 44.3 ha (76.4 %), 44.7 ha (82.2 %) and 55.7 ha (96.0 %) of the irrigation field are moderately suitable for jute mallow, tomato and cabbage production respectively. The major limiting factors for the crops were high BD and acidity levels. The AHP proved to be a very useful tool for the incorporation of farmers’ views into decision making about the suitability of soils for crop production.